Pengaruh Hasil Fraksinasi Ekstrak Daun Kemangi (Ocimum sanctum L.) Terhadap Aktivitas Susunan Saraf Pusat Pada Mencit Putih Jantan - Rahimatul Uthia; Helmi Arifin; Feni Efrianti (Jurnal Farmasi Higea, 2017)
Study about activity of the central nervous system stimulant of  breadfruit’s leaf the water fraction Ocimum santum L. Using experimental animals  male white mice (Mus musculus, L) has been done. Breadfruit’s leaf the water fraction at a dose of 25 mg/kg BW, 50 mg/kg BW and 100 mg/kg BW given to mice orally 15 days. Stimulant activity was tested on day -5, -10 and -15. As a comparison used caffeine 13 mg/kg BW while luminal 50 mg/kg BW is used to test a long sleep induction and sleep in mice. Parameters used stimulant activity is endurance test with Rotary road equipment, test sensor activity and test motor activity wiht a Automotic hole board and sleep induction test and a long sleep. From the research that has been done, it is know that kemangi leaf the water fraction at a 25 mg/kg BW, 50 mg/kg BW and 100 mg/kg BW have a central nervous system stimulan activity by increasing endurance, sensor activity and motor activity as well as increase the time to accelerate the induction of sleep and long sleep in mice sigficantly (P>0,05).